Studies on conducting polymer electroactive paper actuators: effect of humidity and electrode thickness - Deshpande, S. D.; Kim, Jaehwan; Yun, Sung-Ryul (Smart Materials & Structures, 2005)
Actuators based on cellulose paper with conducting polymer (CP-EAPap) as an electrode material were constructed. The bilayer and trilayer types of actuators were fabricated by depositing conducting polypyrrole on one side and two sides of cellophane paper respectively, which was previously gold coated. By varying the deposition time, the electrode thickness was manipulated. The performance of these two types of actuators was compared with respect to humidity changes and thickness variation. The electrode thickness plays a key role in the displacement behavior of these types of actuators. The best performance at higher humidity is also characteristic of CP-EAPap actuators. The possible mechanism of actuation is addressed in this paper.

Synthesis, characterization and actuation behavior of polyaniline-coated electroactive paper actuators - Kim, Jaehwan; Yun, Sung-Ryul; Deshpande, S. D. (Polymer International, 2007)
This investigation deals with the synthesis, characterization and actuation behavior of conductive polyaniline-coated electroactive paper actuators. The actuator is made by electrochemical deposition of conductive polyaniline on a cellulose paper. The aim of the investigation was to improve the bending displacement of electroactive paper actuators. The displacement outputs of the actuators show that a trilayer is better than a bilayer configuration. The nature of the dopant ion used in the electro-generation affects the performance. A change in humidity plays a vital role in actuation performance of the actuators. Comparing the performance of electroactive paper actuators with and without a conductive polyaniline coating, the coating improves the displacement output threefold. Finally, the actuation principle mechanism is addressed. (C) 2007 Society of Chemical Industry.
Keywords: bending actuator; conducting polymer; electroactive polymer (EAP); polyaniline